IMPORTANCE OF ATTRACTING INVESTMENTS IN INDUSTRIES OF THE NATIONAL ECONOMY - Khakimov, Doston Allaberdi ugli; Sabirova , L.Sh. (Educational Research in Universal Sciences, 2023)
The article provides an in-depth analysis of the regional features of investment activities in Uzbekistan. Scientifically based proposals and recommendations have been developed on the need to pay attention to important aspects of investment activities in the effective conduct of investment activities in the regions, the formation and gradual improvement of investment attraction mechanisms, the establishment and sustainable development of investment funds to increase local investment activity.